11 years' follow-up of trastuzumab after adjuvant chemotherapy in HER2-positive early breast cancer: final analysis of the HERceptin Adjuvant (HERA) trial. Issue 10075 (25th March 2017) - Cameron, David; Piccart-Gebhart, Martine J; Gelber, Richard D; Procter, Marion; Goldhirsch, Aron; de Azambuja, Evandro; Castro, Gilberto; Untch, Michael; Smith, Ian; Gianni, Luca; Baselga, Jose; Al-Sakaff, Nedal; et al.
Summary: Background: Clinical trials have shown that trastuzumab, a recombinant monoclonal antibody against HER2 receptor, significantly improves overall survival and disease-free survival in women with HER2-positive early breast cancer, but long-term follow-up data are needed. We report the results of comparing observation with two durations of trastuzumab treatment at a median follow-up of 11 years, for patients enrolled in the HERA (HERceptin Adjuvant) trial. Methods: HERA (BIG 1-01) is an international, multicentre, open-label, phase 3 randomised trial of 5102 women with HER2-positive early breast cancer, who were enrolled from hospitals in 39 countries between Dec 7, 2001, and June 20, 2005. After completion of all primary therapy (including, surgery, chemotherapy, and radiotherapy as indicated), patients were randomly assigned (1:1:1) to receive trastuzumab for 1 year (once at 8 mg/kg of bodyweight intravenously, then 6 mg/kg once every 3 weeks) or for 2 years (with the same dose schedule), or to the observation group. Primary endpoint is disease-free survival, and analyses are in the intention-to-treat population. Hazard ratios (HRs) were estimated from Cox models, and survival curves were estimated by the Kaplan-Meier method. Comparison of 2 years versus 1 year of trastuzumab is based on 366-day landmark analyses. This study is registered withClinicalTrials.gov (NCT00045032 ). Findings: Of the 5102 women randomly assigned in the HERA trial, three patients had no evidence of having provided written informed consent to participate. We followed up the intention-to-treat population of 5099 patients (1697 in observation, 1702 in 1-year trastuzumab, and 1700 in 2-years trastuzumab groups). After a median follow-up of 11 years (IQR 10·09–11·53), random assignment to 1 year of trastuzumab significantly reduced the risk of a disease-free survival event (HR 0·76, 95% CI 0·68–0·86) and death (0·74, 0·64–0·86) compared with observation. 2 years of adjuvant trastuzumab did not improve disease free-survival outcomes compared with 1 year of this drug (HR 1·02, 95% CI 0·89–1·17). Estimates of 10-year disease-free survival were 63% for observation, 69% for 1 year of trastuzumab, and 69% for 2 years of trastuzumab. 884 (52%) patients assigned to the observation group selectively crossed over to receive trastuzumab. Cardiac toxicity remained low in all groups and occurred mostly during the treatment phase. The incidence of secondary cardiac endpoints was 122 (7·3%) in the 2-years trastuzumab group, 74 (4·4%) in the 1-year trastuzumab group, and 15 (0·9%) in the observation group. Interpretation: 1 year of adjuvant trastuzumab after chemotherapy for patients with HER2-positive early breast cancer significantly improves long-term disease-free survival, compared with observation. 2 years of trastuzumab had no additional benefit. Funding: F Hoffmann-La Roche (Roche).